FAKTOR-FAKTOR YANG MEMPENGARUHI CAPITAL STRUCTURE SEKTOR AGRIKULTUR - WIZAYA, MARCELLA PUTRI; DEITIANA, TITA (E-Jurnal Manajemen Trisakti School of Management (TSM), 2021)
A company must exercise caution when making financial decisions depending on its capital structure. Because a company's value is directly affected by its capital structure. Therefore, company must consider about determinant factors in order to create an optimal combination of debt and equity. There are profitability, liquidity, size, tangibility, and growth. The purpose of this study is to examine empirically the impact of profitability, liquidity, size, tangibility, and growth on capital structure. This study uses annual financial report data from 8 agricultural sector companies listed on the Indonesia Stock Exchange (IDX) in from 2013 to 2020, which were selected using the purposive sampling method. This research employs a data analysis method known as multiple regression analysis with a panel data approach. The results showed that profitability and liquidity variables had a negative effect on capital structure, but other variables—firm size, tangibility and growth—had no effect on capital structure.